The association between changes in cerebral hemodynamics and cerebrovascular complications during ECMO treatment in neonates. - Jian-Feng Liu; Yi-Nan Liu; Ya-Ting Zeng; Zhe-Yuan Gao; Heng Cai; Yi-Rong Zheng; Qi-Liang Zhang; Qiang Chen (PLoS ONE)
Objective To investigate whether changes in cerebrovascular hemodynamic parameters during extracorporeal membrane oxygenation (ECMO) treatment in neonates are associated with the occurrence of cerebrovascular complications. Methods This study selected neonatal patients who received ECMO treatment at a pediatric hospital in China from June 2021 to June 2024. Relevant clinical data were collected from the electronic medical record system. Data from cranial ultrasound examinations before and during ECMO treatment, as well as the occurrence of cerebrovascular complications, were collected for further analysis. Results A total of 37 neonates were enrolled in this study. Among them, 15 neonates who developed cerebrovascular complications during ECMO were included in the complication group, while the remaining 22 neonates were included in the non-complication group. The age difference between the two groups was statistically significant. The systolic blood pressure coefficient of variation (SBP-CV) and diastolic blood pressure CV (DBP-CV) were significantly higher in the complication group compared to the non-complication group. Additionally, the anterior cerebral artery peak systolic velocity CV (ACA-PSV-CV) and ACA resistance index CV (ACA-RI-CV) were significantly higher in the complication group than in the non-complication group. However, there was no significant difference in the ACA end-diastolic velocity CV (ACA-EDV-CV) between the two groups. The receiver operating characteristic (ROC) curve analysis of risk factors for cerebrovascular complications indicated that the area under the curve (AUC) for ACA-RI-CV was 0.765 (95% CI: 0.608-0.923, p = 0.007). The AUC for ACA-SBP-CV was 0.815 (95% CI: 0.666-0.964, p = 0.001). Moreover, when ACA-RI-CV and ACA-SBP-CV were combined, the AUC was 0.873 (95% CI: 0.758-0.988, p<0.001). Conclusion High ACA-RI-CV and ACA-SBP-CV were associated with the occurrence of cerebrovascular complications during ECMO treatment in neonates. The combined detection of ACA-RI-CV and ACA-SBP-CV had a predictive role in the early identification of cerebrovascular complications in neonatal ECMO patients.